EFEKTIVITAS LAYANAN INFORMASI MENGGUNAKAN PENDEKATAN DISCOVERY LEARNING DALAM MENINGKATKAN ASPIRASI KARIER SISWA - RAMADHANI, ERFAN (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACTCareer aspiration is very important for students because career aspiration is the desire or hope, ideals, ambitions, and dreams that realistic individuals against certain achievements in the future. Career aspiration are associated with the primary desire of the individual, and an achievement that would like tried to be achieved. Based on the facts found in the field, the low high school graduates who do not attend school to college. In fact, the phenomenon had been contradiction with the high school purpose to continue their education to a higher level. That phenomenon is an indication that the students career aspirations are in the low category. One of the efforts to improving the students career aspiration is within information service. This study aimed to test the effectiveness of information services using discovery learning approach in improving students career aspiration. This study uses quantitative methods using Quasi Non Randomized Experiment with the design of pretest-posttest control group design. Subjects were students of SMAN 8 Padang as an experimental group and a students at SMAN 7 Padang as the control group. The research instrument used was Likert Scale models, then be analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov test Two Independent Samples with SPSS version 17.00. The findings of this research generally indicates that the information service using discovery learning approach is effective in improving students career aspirations. Furthermore, research findings in particular that: (1) there are significant differences career aspiration in the students the experimental group before and after the information service using the approach of discovery learning, (2) there is a difference career aspiration in the control group before and after the information service without using the approach of discovery learning, (3) there is a difference career aspiration between the experimental group students were given information services using discovery learning approach to the control group were given the information service without using discovery learning approach. Based on the results of the study showed that the experimental group and the control group had increased scores in career aspirations but the experimental group experienced a greater improvement than the control group. Furthermore, based on the results of this study that can be suggested to the parties concerned to be able to work together to help students improve their career aspirations.Keywords: Career Aspiration of Students, Information Services, Discovery Learning